Implementasi Kebijakan Program Sekolah Penggerak dalam Kerangka Merdeka Belajar di SMP Negeri 1 Tlogomulyo Temanggung - Harningsih, Lilis Sri; Nurkolis, Nurkolis; Sudana, I Made (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
Based on government policy regarding the driving school program, only 5 schools have implemented the program in Temanggung district. This prompted this research to be carried out at SMP Negeri 1 Tlogomulyo as one of the implementers of the 1st generation driving school program. The unique advantage of SMP Negeri 1 Tlogomulyo Temanggung is the enthusiasm of all school members in implementing every new policy, even though the school is in a sub-district area. With good communication by the school principal, he is able to convince the school community to take part in becoming agents of change in achieving educational goals. The aim of this research is to describe communication, resources, disposition and bureaucratic structure in the implementation of driving school policies. Data collection through observation, interviews and documentation studies as supporting data. The data analysis process goes through three stages, namely data reduction, data presentation and drawing conclusions/verification. To check the validity of the data, researchers used the triangulation method. The results of the research show that SMP Negeri 1 Tlogomulyo has actually implemented the policy and how to implement the policy of the driving school program within the independent learning framework which has been running for 3 years at SMP Negeri 1 Tlogomulyo Temanggung through five interventions: (a) Consultative and asymmetric assistance (b) Strengthening human resources (c) Learning with a new paradigm (d) Based planning, (e) Digitalization of schools.